2003
DOI: 10.5194/angeo-21-437-2003
|View full text |Cite
|
Sign up to set email alerts
|

First results obtained by the Cluster STAFF experiment

Abstract: Abstract. The Spatio Temporal Analysis of Field Fluctuations (STAFF) experiment is one of the five experiments, which constitute the Cluster Wave Experiment Consortium (WEC). STAFF consists of a three-axis search coil magnetometer to measure magnetic fluctuations at frequencies up to 4 kHz, a waveform unit (up to either 10 Hz or 180 Hz) and a Spectrum Analyser (up to 4 kHz). The Spectrum Analyser combines the 3 magnetic components of the waves with the two electric components measured by the Electric Fields an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
165
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 203 publications
(167 citation statements)
references
References 43 publications
(35 reference statements)
2
165
0
Order By: Relevance
“…These data can be used for spectrum analysis, spectral matrices, wave normal analysis, and Poynting flux calculations on the ground. Second, the waveforms can be analyzed in the Waves FFT Engine coprocessors to produce spectral matrices similar to those computed on the Cluster STAFF instrument (Cornilleau-Wehrlin et al 2003) which can be generalized to other instances .…”
Section: Waves Receiversmentioning
confidence: 99%
“…These data can be used for spectrum analysis, spectral matrices, wave normal analysis, and Poynting flux calculations on the ground. Second, the waveforms can be analyzed in the Waves FFT Engine coprocessors to produce spectral matrices similar to those computed on the Cluster STAFF instrument (Cornilleau-Wehrlin et al 2003) which can be generalized to other instances .…”
Section: Waves Receiversmentioning
confidence: 99%
“…Magnetic field fluctuations are measured by the search coils (SC) of the STAFF experiment with 0.04 s time resolution (Cornilleau-Wehrlin et al, 2003). This instrument measures magnetic fluctuations above 0.1 Hz.…”
Section: Magnetosheath Spectrum In the Presence Of Alfvén Vorticesmentioning
confidence: 99%
“…They addressed the location of noise with respect to the equatorial plane and the spatio-temporal structure of its frequency spectra. Santolík et al (2002) found these waves within 2 • of the magnetic equator, and Cornilleau-Wehrlin et al (2003), in another case, at about 3 • of the model equator, with an extension of 0.15 R E in the direction perpendicular to the ecliptics. Since a common feature of the equatorial noise is the presence of harmonic lines whose spacings do not match the local (a) sum of the power-spectral densities of the three magnetic components, (b) sum of the power-spectral densities of the two electric components ; (c) ellipticity and (d) planarity are determined using the singular value decomposition of the magnetic spectral matrix.…”
Section: Introductionmentioning
confidence: 99%